The Nexus between Ethnic Reconciliation and Security Issues in Post-War Sri Lanka: A Study on Issues of Rehabilitation and Reintegration of Former Combatants - Chandran, Shamini (My University, 2015)
The central theme of this paper is to bring about a new framework to the connection between security and reconciliation for ethnic' reconciliation in the issue of rehabilitation and reintegration of ex-combatants after the lengthy war in Sri Lanka. Regarding the issue of security which had severe psychological impacts, bringing genuine reconciliation seems to be an extremely challenging task. Reconciliation in this study is understood as a way for transforming conflict and facilitating psychological change that can lead to stable peace. Due to the link between security and reconciliation, this paper strongly emphasizes that neglecting the feeling of insecurity will lead to more hardships and challenges in promoting reconciliation in post-war periods. This is evident when looking at the current situation in Sri Lanka, because, the main causes and effects are due to security elements which flared up negative attitudes among the different ethnic groups. This is an obstruction for reconciliation. Therefore, constructive efforts that are needed will undoubtedly facilitate psychological changes within the ethnic groups. This paper argues that with regard to the issue of security, the psychological impacts of the different ethnic groups have still not been transformed in a positive way. Therefore, it has become a factor hindering the promotion of a true reconciliation process. Though the government has taken measures for the betterment of the current situation, this study found that those measures are not feasible enough to be implemented due to security sequences.
Keywords: Reconciliation, Security, Rehabilitation, Reintegration, Ex-combatants